Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Genetic diversity of a flightless dung beetle appears unaffected by wildfire - Ryan Shofner; William Sherwin; Chris Reid; Aidan Runagall-McNaull; Gerasimos Cassis; Shawn Laffan (Journal of Insect Conservation, 2023)
The wildfires of Australia’s Black Summer in 2019/2020 caused a massive loss of wildlife and habitats, but the effects of the fire on invertebrate species post-burn are unknown. We hypothesised that the fires would negatively affect the genetic diversity of invertebrate species by impeding movement between populations due to habitat loss. We studied the genetic diversity of a flightless dung beetle, Amphistomus primonactus Matthews 1974, to determine the impact of the wildfires on this species. We examined 90 SNPs from 193 individuals across seven localities impacted by the wildfires in north-eastern New South Wales. We used STRUCTURE to determine the overall population structure of the seven localities. We calculated four within-locality genetic diversity measures (observed heterozygosity ( H o ), unbiased expected heterozygosity (u H e ), Shannon’s Information ( 1 H ), and the inbreeding coefficient ( F IS ). We calculated three between-locality genetic diversity measures (Fixation Index ( F ST ), Hedrick’s G” ST , and Shannon’s Mutual Information ( I ). We used partial Mantel tests to compare the between-locality genetic diversity measures with the mean fire intensity along each pairwise linear transect, while accounting for genetic variation due to geographic distance. We compared the within-locality genetic diversity measures to the mean fire intensity at each site. STRUCTURE showed a large degree of intermixing between localities. We found no significant effect of fire on any within-locality genetic diversity measure, or on any between-locality genetic diversity measure. We suggest that the genetic diversity of A. primonactus was not significantly affected by the Black Summer wildfires. Implications for insect conservation: Our results show that the 2019/2020 wildfires had a negligible impact on the genetic structure of A. primonactus . This offers a promising outlook for the species in its recovery from the fires.